Square dance, loneliness, quality of life, and attitude toward aging in middle-aged and older women in China - Li, Ruitong; Yan, Qin; Qu, Yujia; Wang, Yan (Frontiers in Public Health, 2025)
BackgroundWith the ongoing advancement of society and the economy, population aging has emerged as an unavoidable global trend, leading to various social issues and exerting a profound impact on the physical and mental well-being of middle-aged and older adults. While women often face greater challenges than men during the aging process, particularly in terms of physical health vulnerabilities, mental health disparities and socioeconomic disadvantages. These factors underscore the importance of studying middle-aged and older women to better address their unique needs and promote healthy aging. Much attention has been paid to how middle-aged and older women can improve healthy aging, positive emotions and subjective well-being through regular physical activity.MethodsUsing 4,819 middle-aged and older women who participated in square dance exercise, structural equation modeling was used to explore the relationship between square dance exercise and attitude toward aging, as well as the chain-mediated effects of loneliness and quality of life.Results(a) Square dance exercise is a positive predictor of attitude toward aging in middle-aged and older women. (b) Loneliness and quality of life moderated the relationship between square dance exercise and attitude toward aging, and their mediating effects included three pathways. (c) The single mediating effect of quality of life was the largest compared to the chain mediating effects of loneliness and loneliness-quality of life.ConclusionThis study aimed to reveal the reduction of loneliness and improvement of quality of life as potential mechanisms in the relationship between square dance exercise and attitude toward aging, and to emphasize that square dance exercise can be effective in promoting positive attitude toward aging and enhancing subjective well-being in middle-aged and older women.